Long-Term Field Performance of Pervious Concrete Pavement - Aleksandra Radlińska; Andrea Welker; Kathryn Greising; Blake Campbell; David Littlewood (Advances in Civil Engineering)
The work described in this paper provides an evaluation of an aged pervious concrete pavement in the Northeastern United States to provide a better understanding of the long-lasting effects of placement techniques as well as the long-term field performance of porous pavement, specifically in areas susceptible to freezing and thawing. Multiple samples were taken from the existing pavement and were examined in terms of porosity and unit weight, compressive and splitting tensile strength, and the depth and degree of clogging. It was concluded that improper placement and curing led to uneven pavement thickness, irregular pore distribution within the pervious concrete, and highly variable strength values across the site, as well as sealed surfaces that prevented infiltration.